PERAN LABA KOTOR, AKTIVITAS OPERASIONAL, AKTIVITAS INVESTASI, DAN AKTIVITAS PENDANAAN ARUS KAS TERHADAP RETURN SAHAM - Ditya Wardana; Satya Fauziah (Riset Akuntansi)
This research aims to  analyze the effects of gross profit, and cashflow activity on stock returns  by taking the population of this study, namely consumer goods companies listed on the Indonesia Stock Exchange in 2018-2019. In order to find 30 organizations that fit the criteria for the research sample, a purposive sampling method was utilized in the sampling process. SPSS is used for data analysis, including multiple regression and hypothesis testing.